Peran Guru Pesantren dalam Tranformasi Etika Santri Melalui Pembelajaran Kitab Ta'lim Muta’allim di Pondok Pesantren Raudlatul Muttaqin Talun Sidogembul Sukodadi Lamongan (AJER: Advanced Journal of Education and Religion, 2024)
Teachers at Islamic boarding schools (pondok pesantren) not only serve as educators but also as role models and mentors in the application of values taught in the book Ta'lim Muta'allim. They function as role models, providing a living example of the implementation of Islamic manners and ethics. The term "transformation" originates from the English word "transform”, which means to change form or appearance. Etymologically, it refers to a change in form or manifestation. In a broader sense, transformation is a change into another form while retaining the same values. The objectives of this research are: 1) to describe the role of teachers in the transformation of students' ethics through the study of the Ta'lim Muta'allim book, and 2) to describe the transformation of students' ethics in studying the Ta'lim Muta'allim book. This research employs a qualitative method with a descriptive approach. The data collection techniques used are observation, interviews, and documentation. The results of the research indicate that: 1) The role of teachers in the transformation of students' ethics through the study of the Ta'lim Muta'allim book is crucial in shaping and strengthening the Islamic foundation of the students. As educators in the pesantren, teachers are not only responsible for teaching religious subjects but also serve as spiritual guides, constantly accompanying students in internalizing Islamic values. 2) The transformation of students' ethics in studying the Ta'lim Muta'allim book occurs significantly. Students experience positive changes in their attitudes, behavior, and understanding of the importance of manners in the teaching and learning process.